2023
DOI: 10.1002/ange.202215544
|View full text |Cite
|
Sign up to set email alerts
|

Frustration in Super‐Ionic Conductors Unraveled by the Density of Atomistic States

Abstract: The frustration in super‐ionic conductors enables their exceptionally high ionic conductivities, which are desired for many technological applications including batteries and fuel cells. A key challenge in the study of frustration is the difficulties in analyzing a large number of disordered atomistic configurations. Using lithium super‐ionic conductors as model systems, we propose and demonstrate the density of atomistic states (DOAS) analytics to quantitatively characterize the onset and degree of disorderin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…It is possible that the soft degrees of freedom for libration of the PS 4 units as seen in several polymorphs further generate the distribution of temporary site energies which leads to low energy barrier percolation pathways . Similarly, Wang and co-workers found that adding Br into Li 3 YCl 6 to form Li 3 YBr 1.5 Cl 4.5 introduced a larger variety of closely spaced octahedral Li site energy levels, leading to a lower order–disorder transition temperature and increased Li conductivity . These previous studies highlight that engineering a more uniform Li site energy landscape can facilitate more facile Li-ion migration since there is a greater probability that neighboring sites are close in energy, which in turn can lead to lower energy barriers for Li hopping between them.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is possible that the soft degrees of freedom for libration of the PS 4 units as seen in several polymorphs further generate the distribution of temporary site energies which leads to low energy barrier percolation pathways . Similarly, Wang and co-workers found that adding Br into Li 3 YCl 6 to form Li 3 YBr 1.5 Cl 4.5 introduced a larger variety of closely spaced octahedral Li site energy levels, leading to a lower order–disorder transition temperature and increased Li conductivity . These previous studies highlight that engineering a more uniform Li site energy landscape can facilitate more facile Li-ion migration since there is a greater probability that neighboring sites are close in energy, which in turn can lead to lower energy barriers for Li hopping between them.…”
Section: Discussionmentioning
confidence: 93%
“…54 Similarly, Wang and co-workers found that adding Br into Li 3 YCl 6 to form Li 3 YBr 1.5 Cl 4.5 introduced a larger variety of closely spaced octahedral Li site energy levels, leading to a lower order− disorder transition temperature and increased Li conductivity. 55 These previous studies highlight that engineering a more uniform Li site energy landscape can facilitate more facile Li-ion migration since there is a greater probability that neighboring sites are close in energy, which in turn can lead to lower energy barriers for Li hopping between them. This is not a sufficient condition for high conductivity, as the component of the migration energy that is independent of the site energy also needs to be small.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Currently, the most promising method would be to develop and use machine-learned potentials. Recently, various machine-learning potentials, such as neural network potential (NNP), 36 deep potential (DP), 37,38 Gaussian approximation potential (GAP), 39 spectral neighbor analysis potential (SNAP), 40 and moment tensor potential (MTP) 41 have been reported. We chose the MTP among various machine learning potentials because, in terms of both performance and computational cost, it is acknowledged as the most reasonable method.…”
Section: Introductionmentioning
confidence: 99%
“…The DPMD method is a significant milestone in atomistic simulation for materials because it has demonstrated high accuracy similar to that of DFT and competitive efficiency with CMD for different systems. 33–36 Successful applications of DPMD on molten salt simulations began in 2020, focusing on ZnCl 2 and its mixtures. In their study, Pan et al conducted a comparison of the partial radial distribution functions, partial structure factors, and coordination numbers using the DPMD and PIM potentials.…”
Section: Introductionmentioning
confidence: 99%